Mobility, Retention and Productivity of Genomics Scientists in the United States - HUANG, Kenneth Guang-Lih (Institutional Knowledge at Singapore Management University, 2014)
Scientific and technological innovations by highly skilled scientists and inventors are critical to the long-term economic health of the United States. These scientists enable the creation and flow of scientific research and technologies from public institutions such as universities to private firms and vice versa by forming vital linkages between them. The exchange of new ideas and the commercialization of promising scientific and technological innovations have resulted in the formation of new high-technology startups, growth opportunities within entrepreneurial and established science-based firms, and jobs creation. These form the backbone of the scientific innovation ecosystem in the United States. A potential brain drain of scientists and inventors from the United States, or a failure to attract them to the United States at previous levels, could challenge its leading role in science and technology, and undermine its long-term economic resilience.